Intercultural Competences in Health Care - Judaism - Bernaciak, Elżbieta; Lemska, Magdalena; Mędrzycka-Dąbrowska, Wioletta; Szulkowska, Żanetta (Journal of Education, Health and Sport, 2019)
The present times and Poland’s entry into the European Union, the opening of borders, has intensified the phenomenon of migration of the population and contact between different cultures. In Poland, national minorities have been living since the dawn of time, but the current situation has a different dimension. Until now, the term "Transculturality" was not known in our country. However, the influx of people from the remotest parts of the world caused a situation requiring medical personnel to perceive the patient through the prism of biological, social and psychological needs as well as from the angle of other religions. Problems that appear taking care of such patients have caused that I decided to look at this issue on the example of Judaism believers. The aim of my work is to get the opinion of health professionals about intercultural competences in direct care of these patients.